Dietary Sucrose Determines Stress Resistance, Oxidative Damages, and Antioxidant Defense System in Drosophila - Olha Strilbytska; Tetiana Strutynska; Uliana Semaniuk; Nadia Burdyliyk; Volodymyr Bubalo; Oleh Lushchak (Scientifica)
Varied nutritional interventions affect lifespan and metabolic health. Abundant experimental evidence indicates that the carbohydrate restriction in the diet induces changes to support long-lived phenotypes. Reactive oxygen species (ROS) are among the main mechanisms that mediate the effect of nutrient consumption on the aging process. Here, we tested the influence of sucrose concentration in the diet on stress resistance, antioxidant defense systems, and oxidative stress markers in D. melanogaster. We found that high sucrose concentration in the fly medium leads to enhanced resistance to starvation, oxidative, heat, and cold stresses. However, flies that were raised on low sucrose food displayed increased levels of low-molecular-mass thiols, lipid peroxides in females, and higher activity of antioxidant enzymes, indicating that the consumption of a low carbohydrate diet could induce oxidative stress in the fruit fly. We found that the consumption of sucrose-enriched diet increased protein carbonyl level, which may indicate about the activation of glycation processes. The results highlight a strong dependence of oxidative metabolism in D. melanogaster from dietary carbohydrates.